Unveiling the Clinical Path of Microinvasive Breast Cancer: A Comparative Study With Tis‐T1 Breast Cancer - Ran Song; Dong‐Eun Lee; So‐Youn Jung; Seeyoun Lee; Han‐Sung Kang; Jai Hong Han; Jaeyeon Woo; Eun‐Gyeong Lee (Cancer Medicine)
ABSTRACT Purpose The prognosis of microinvasive breast cancer (MIBC) is controversial, with a high reported rate of local recurrence (LR). This study aimed to evaluate the characteristics, treatments, and prognosis of patients with MIBC compared to those with carcinoma in situ (CIS) or early invasive cancer. Methods Patients who diagnosed with CIS or stage I breast cancer were retrospectively enrolled. Using the Kaplan–Meier method, local recurrence‐free survival (LRFS), systemic recurrence‐free survival (SRFS), and cancer‐specific survival (CSS) were compared according to T stage. The prognostic factors associated with LRFS were identified using the Cox proportional hazards model. Results According to T stage, 517 (21.6%), 200 (8.4%), 207 (8.7%), 363 (15.2%), and 1101 (46.1%) patients had Tis, T1mi, T1a, T1b, and T1c tumors, respectively. The proportion of human epidermal growth factor receptor 2‐positive tumors was significantly higher in patients with MIBC (p < 0.0001). The administered adjuvant treatments also showed differences according to T stage (p < 0.0001). During the 73‐month median follow‐up period, patients with MIBC showed significantly worse LRFS than those with T1a or T1c tumors (p = 0.002). There was no significant difference in SRFS and CSS. In the Cox regression analysis, tumor multiplicity (p = 0.017), Ki‐67 (p = 0.025), cancer subtype (p = 0.034), adjuvant endocrine therapy (p = 0.003), and adjuvant radiation therapy (p < 0.0001) were significant prognostic factors associated with LRFS. Conclusion The risk of LR was higher in patients with MIBC than in those with small invasive breast cancer. Therefore, if indicated, adjuvant endocrine and radiation therapies should be administered to prevent undertreatment in patients with MIBC.